PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN PROFITABILITAS PADA STRUKTUR MODAL PERUSAHAAN - Devita Angelina, Kadek Irrine; Mustanda, I Ketut (E-Jurnal Manajemen, 2016)
The aim of this study was to determine the significance of the partial influence of the size of companies, growth in sales and profitability is proxied by Return on Assets (ROA) in the capital structure. The population used in this study is the food and beverage companies listed in Indonesia Stock Exchange 2010-2013 period totaling 18 companies. Saturated sampling method is used as a determination of the number of samples in this study. The data in this research is multiple linear regression using SPSS in data processing. Results of the study found that the size of the company's partial significant positive effect on the capital structure, sales growth significantly positive effect on the capital structure and profitability is proxied by Return on Assets (ROA) significant negative effect on the capital structure .
Keywords: capital structure, firm size, sales growth, profitability